A comprehensive study on protection, control and communication techniques: a key concept for microgrid intelligent operation - Mahesh, C; T.Josh, F; Sanjeevi Gandhi, A (International Journal of Engineering and Technology, 2018)
Microgrid is an integrated network of renewable and non renewable resources to supply the green power to a small range of community. An effective communication technology is necessary to be implemented among the power generations, storages and loads of microgrid in order to manage the load sharing, shedding and protection issues. This paper provides the study on architecture, characteristics, load managements, protection schemes, communication techniques and research challenges of microgrid.